Analisis Peranan Guru Penggerak dalam Membantu Mensukseskan Implementasi Kurikulum Merdeka pada Sekolah Dasar SDN 19 Peninjau - Wila Yurnita; Masbirorotni Masbirorotni; Mulyadi Mulyadi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This research aims to analyze the role of Driving Teachers in helping to make the implementation of the Merdeka Curriculum successful in the 19 Peninjauan Elementary Schools (SD). The Independent Curriculum is an educational policy that aims to provide freedom to educational units in designing learning that is more flexible, meaningful and in accordance with the needs of students. Mobilizing Teachers, as agents of change, are expected to play an important role in the successful implementation of this curriculum. The research method used in this research is qualitative with a literature review approach. The results of the research show that the Mobilization Teacher at SDN 19 Peninjau acts as a learning facilitator, leader of change, and motivator for his colleagues in the successful implementation of the Merdeka Curriculum. Mobilizing Teachers not only focus on teaching in the classroom, but also play an active role in developing the professionalism of other teachers and establishing a school culture that supports the principles of the Independent Curriculum. However, challenges such as limited resources, uneven understanding of the Independent Curriculum, and resistance to change are still the main obstacles.